The border condition in El amigo del desierto by Pablo d'Ors (XXI Century. Spanish Literature and Culture, 2019)
In his novel El amigo del desierto, Pablo d'Ors provides an answer to the tragic condition of uprootedness of the postmodern subject and shows a path to recover a sense of being at home. In my analysis I use the Spanish thinker Eugenio Trías’ theoretical framework of the philosophy of limit. Drawing on Trías’ ideas on the existential border condition of the human being I will show how El amigo del desierto’s main character is able to rise above the limits of his familiar world and to discover a place to feel at home in the most unusual and inhospitable land.
Keywords: Spanish literature; Pablo d'Ors; Eugenio Trías; border condition; postmodernity; contemplation